Crystal structure of 5-(adamantan-1-yl)-3-[(4-{[2-(trifluoromethyl)phenyl]-methyl}piperazin-1-yl)methyl]-1,3,4-oxadiazole-2(3H)-thione, C25H31F3N4OS - Al-Wahabi, Lamya H.; Abdelbaky, Mohammed S. M.; Garcia-Granda, Santiago; Tiekink, Edward R. T. *; El-Emam, Ali A. (De Gruyter Open, 2023)
C25H31F3N4OS, monoclinic, P21/c (no. 14), a = 6.7323(1) Å, b = 15.4999(2) Å, c = 23.7905(4) Å, β = 93.037(2)°, V = 2479.05(6) Å3, Z = 4, Rgt(F) = 0.0473, wRref(F2 ) = 0.1394, T = 293 K. CCDC no.: 2240574